PENDIDIKAN AGAMA ISLAM PERSPEKTIF TEORI INTERNASIONALISME SIMBOLIK - Diah Ainun Khafidloh; Wirdatul Hasanah; Asnawan; Siti Muthiatun Najiyah; Siti Aminah (PT. Hasba Edukasi Mandiri, 2026)
This study aims to analyze Islamic Religious Education from the perspective of symbolic interactionism theory. This approach emphasizes that students’ religious understanding is formed through social interactions with teachers, peers, families, and the surrounding community. This research employed a qualitative method with a library research approach. The data were collected from various literature sources such as books, journals, and scientific documents related to symbolic interactionism and Islamic education. The results indicate that the application of symbolic interactionism theory in Islamic Religious Education learning creates a more dialogical, contextual, and meaningful learning process. Teachers play an important role as facilitators in building positive symbolic interactions so that Islamic values can be internalized in students’ daily lives. Furthermore, this approach positively contributes to the development of religious character such as honesty, discipline, responsibility, and social awareness.